Concentration threshold for polyethylene microplastics impacting nitrogen transfor-mation in heterotrophic nitrification-aerobic denitrification systems - Xue Bai; Mengying Yi; Lang Ran; Weidong Xiao; Ran Sun; Zherui Zhang; Sihai Hu; Yaoguo Wu (Bioresource Technology, 2027)

Discriminating scheelite deposit types using interpretable ensemble learning: A case study from the Xuefengshan Au-Sb-W belt, South China - Xiao-Ran Zhou; Qi-Liang Liu; Biao Liu; Jing-Hua Wu; Safiyanu Muhammad Elatikpo; Fei Deng; Shiwei Cui (Journal of Geochemical Exploration, 2026)

Selective enrichment of fractions in thermal dissolution of high-sulfur coal: Application of solid-phase microextraction technology and construction of ZnO/rGO coatings - Jia-Qi Liu; Xing Fan; Ran-Ran Hou; Xiao-Hui Cao; Binoy K. Saikia; Chao Feng; Jin-Xi Wu; Xiao-Yu Dong (Fuel, 2026)

Pathway-dependent observability of a spring Asian-jet precursor for western North Pacific typhoon activity - Zi-Liang Li; Xiao-Ran Wu (Atmospheric Research, 2026)

Limited enzymatic hydrolysis-mediated assembly of whey protein isolate nanofibers: Influence of protease type and hydrolysis time on fiber formation and β-carotene delivery - Shudong He; Yanni Wu; Tong Jin; Qiming Li; Tianjiao Niu; Xiaodong Cao; Ran Xiao; Hanju Sun; Walid Elfalleh (Food Chemistry, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

Source apportionment and health risk prioritization of groundwater contamination in a coal-mining area: An integrated SOM-PMF-Monte Carlo framework - Zheng Yin; Shiqi Zhang; Xiao Fu; Ran Sun; Ran Lv; Meng Yuan; Ziyuan Gao; Gang Wu (Journal of Environmental Management, 2026)

Experimental and numerical investigation of flow-induced vibration in CMC turbine blades using fluid-structure interaction - Maojing Ran; Lu Zhang; Zhe Liu; Xingshuang Wu; Tianhang Xiao; Xiguang Gao; Yingdong Song (Engineering Structures, 2026)

Decoding the molecular complexity of coal: A machine learning framework for component classification and solvent selection - Yu-Ying Zhou; Xing Fan; Jin-Xi Wu; Zhen-Yu Gao; Ran-Ran Hou; Chao Feng; Zhong-Qiu Liu; Qing Liu; Xiao-Yu Dong; Peng Liang (Fuel, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Offshore wind power prediction based on improved Hankel-DMD-LSTM hybrid model: Strengthening mode selection and residual compensation mechanism - Tengjiao Guo; Qiang Liu; Xingyu Fang; Mingkun Fang; Yanzhao Wu; Ran Tao; Ruofu Xiao (Ocean Engineering, 2026)

Insight into the oxidation mechanism of low-salt Sichuan-style sausages treated with inclusion complexes of tea-polyphenol/β-cyclodextrin/NaCl and electron beam irradiation using machine learning algorithms - Ya Liu; Jiuhong Du; Wenyi Ran; Lihui Huang; Wenyue Yu; Huan Guo; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2026)

AjFOSL Modulates Cell Cycle-Related Genes Associated with Coelomocyte Regeneration in Apostichopus japonicus Evisceration - Ran Xiao; Yinan Wang; Xiaoli Xu; Jiong Wu; Qiang Li (Fishes, 2026)
Apostichopus japonicus undergoes evisceration in response to adverse environmental stimuli, and its coelomocytes undergo rapid regeneration within 6–24 h to restore innate immune function. FOS, an immediate early gene, regulates cell proliferation and cycle, but its role in A. japonicus coelomocyte regeneration after evisceration is unclear. In this study, AjFOSL from A. japonicus was cloned, which harbors a 609 bp open reading frame (ORF) encoding 202 amino acids (aa) with a conserved bZIP domain and is localized on chromosome 14. It shares 58% homology with FOS from Holothuria leucospilota and Lytechinus pictus. Phylogenetic analysis revealed that AjFOSL clusters closely with FOS from Magallana gigas and Mytilus edulis. Tissue distribution analysis showed that AjFOSL was widely expressed in various tissues, with the highest expression level detected in the tentacles. Temporal expression profiling demonstrated that AjFOSL was significantly upregulated by 1.75-fold at 6 h after evisceration. After AjFOSL knockdown, the peak expression of Cyclin A, Cyclin B, and E2F was delayed and the coelomocyte number was consistently reduced compared with that in the evisceration-only group. The AjFOSL acted as an immediate early response gene and was associated with the regulation of coelomocyte regeneration by modulating the expression of cell cycle-related genes. This study provides novel insights into the molecular associations underlying coelomocyte regeneration and the evolutionary adaptation of FOS genes in echinoderms.

Exploring patterns and mechanisms of indigenous microbial community succession driven by polycyclic aromatics in heterotrophic nitrification and aerobic denitrification systems - Weidong Xiao; Yaoguo Wu; Lang Ran; Ran Sun; Sihai Hu; Zherui Zhang; Usman Ghani; Azhar Masaud; Maorui Zhang (Bioresource Technology, 2026)

Nonlinear threshold response and erosion-driven pathways of sediment organic carbon to anthropogenic activities in a large lake - Fengwei Ran; Tao Xiao; Zhongwu Li; Shilan Wang; Yinglong Hou; Haipeng Wu; Xiaodong Nie (Anthropocene, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Correction to: Unveiling the potential of bio-organic fertilizers to enhance crop yield and improve soil and microbial environments: A meta-analysis in China - Xiaofang Huang; Wei Sun; Chengqun Yu; Peili Shi; Junxi Wu; Fadong Li; Ran Xiao; Jialuo Yu; Jiabao Wang; Tao Mu (Plant and Soil, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

A three-step process for purification and stability evaluation of analytical-grade phycocyanin from Spirulina - Hongxiang Zhao; Shilin Wu; Zhen Zhang; Ran Chen; Kun Li; Meicong Xiao; Yunmei Yin; Pei Wang; Rongqing Zhang (Algal Research, 2025)

Response of nitrogen transformation and microbial community to aromatic compounds stress along heterotrophic nitrification and aerobic denitrification process - Weidong Xiao; Ran Sun; Lang Ran; Zherui Zhang; Xue Bai; Chen Lv; Maorui Zhang; Sihai Hu; Yaoguo Wu (Environmental Research, 2025)

Unveiling the potential of bio-organic fertilizers to enhance crop yield and improve soil and microbial environments: A meta-analysis in China - Xiaofang Huang; Wei Sun; Chengqun Yu; Peili Shi; Junxi Wu; Fadong Li; Ran Xiao; Jialuo Yu; Jiabao Wang; Tao Mu (Plant and Soil, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A novel fenton-like catalyst for efficient degradation of tetracycline: Application of the concept of “treating the wastes with wastes” - Lang Ran; Yajuan Zheng; Xu Zhang; Weidong Xiao; Lingxiao Zhu; Junlan Tang; Yaoguo Wu; Lincheng Zhou (Waste Management, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Evaluation of wood vinegar as a green carbon source for heterotrophic nitrification and aerobic denitrification process from performance, mechanism and potential - Weidong Xiao; Yaoguo Wu; Sihai Hu; Zherui Zhang; Lang Ran; Hongjian Luo; Ran Sun (Journal of Environmental Chemical Engineering, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Response of bacterial community structure in saline soils to the application of kitchen waste-derived fermented organic fertilizer - Bin Xie; Wenzhuo Li; Tao Yang; Yajun Zhang; Weidong Xiao; Sihai Hu; Yaoguo Wu; Xiaofeng Sun; Bin wang; Ran Sun (World Journal of Microbiology and Biotechnology, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Paleoceanographic and paleoenvironmental changes in the high-latitude Southern Ocean during late Quaternary: progress and prospects based on the Chinese Antarctic Expeditions - Li Wu; Rujian Wang; Wenshen Xiao; Qingmiao Li; Kaitao Ni; Ran Xu; Yi Chen (Acta Oceanologica Sinica, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Impact of residual antibiotics on microbial decomposition of livestock manures in Eutric Regosol: Implications for sustainable nutrient recycling and soil carbon sequestration - Linfa Fang; Prakash Lakshmanan; Xiaoxuan Su; Yujia Shi; Zheng Chen; Yu Zhang; Wei Sun; Junxi Wu; Ran Xiao; Xinping Chen (Journal of Environmental Sciences, 2025)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

A conductive ionogel with Stretchability, low hysteresis and adjustable adhesion for Air/Underwater mechanosensing - Chuanjiang Zhou; Xiao Song; Ran Wei; Shengjie Liu; Zhaoqiang Wu; Hong Chen (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

New insights into microbial community for simultaneous removal of carbon and nitrogen via heterotrophic nitrification aerobic denitrification process - Weidong Xiao; Guangcai Meng; Chengzhen Meng; Ran Sun; Sihai Hu; Mengying Yi; Xue Bai; Chen Lv; Yaoguo Wu (Journal of Environmental Chemical Engineering, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Association between long-term ozone exposure and readmission for chronic obstructive pulmonary disease exacerbation - Huajing Yang; Zihui Wang; Yumin Zhou; Zhaosheng Gao; Jing Xu; Shan Xiao; Cuiqiong Dai; Fan Wu; Zhishan Deng; Jieqi Peng; Pixin Ran (Environmental Pollution, 2024)

Lightning activity and microphysical structure characteristics during the convective cell mergers in an extreme mesoscale convective system - Jing Sun; Yanjiao Xiao; Yunying Li; Muyun Du; Zhikang Fu; Liang Leng; Ran Cai; Haopeng Wu (Atmospheric Research, 2024)

Promoting nitrogen conversion in aerobic biotransformation of swine slurry with the co-application of manganese sulfate and biochar - Xuan Wu; Xinyu Zhao; Guorong Yi; Wanqiang Zhang; Runyu Gao; Daniel Kuok Ho Tang; Ran Xiao; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Journal of Environmental Management, 2024)

Different binding properties of odorant-binding protein 8 to insecticides in Orius sauteri - Zhe-Ran Wu; Yi-Wen Pei; Xiao-Qing Zhang; Min Lu; Xiao-Long Liu (Pesticide Biochemistry and Physiology, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Polyethylene microplastics induced inflammation via the miR-21/IRAK4/NF-κB axis resulting to endoplasmic reticulum stress and apoptosis in muscle of carp - Tian-jing Liu; Jie Yang; Jia-wei Wu; Xiao-ran Sun; Xue-jiao Gao (Fish & Shellfish Immunology, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Sulfur-aided aerobic biostabilization of swine manure and sawdust mixture: Humification and carbon loss - Yang Wang; Jingwen Wang; Guorong Yi; Xuan Wu; Xiu Zhang; Xu Yang; Kuok Ho Daniel Tang; Ran Xiao; Zengqiang Zhang; Guangzhou Qu; Ronghua Li (Bioresource Technology, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dynamic mode structure analysis of the near-wake region of a Savonius-type hydrokinetic turbine - Yanzhao Wu; Weilong Guang; Ran Tao; Jie Liu; Ruofu Xiao (Ocean Engineering, 2023)

Synergetic effect and mechanism of elementary sulphur, MgSO4 and KH2PO4 progressive reinforcement on pig manure composting nitrogen retention - Yang Wang; Jingwen Wang; Xuan Wu; Ran Zhao; Zengqiang Zhang; Juanjuan Zhu; Muhammad Azeem; Ran Xiao; Junting Pan; Xiu Zhang; Ronghua Li (Environmental Pollution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

The pre-addition of “blocking” proteins decreases subsequent cellulase adsorption to lignin and enhances cellulose hydrolysis - Jingyun Liu; Jie Wu; Yi Lu; Huaiyu Zhang; Qi Hua; Ran Bi; Orlando Rojas; Scott Renneckar; Senqing Fan; Zeyi Xiao; Jack Saddler (Bioresource Technology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

The roles of ETS transcription factors in liver fibrosis - Li-Ye Zhang; Yong Tan; Xiao-Jie Luo; Jiang-Feng Wu; Yi-Ran Ni (Human Cell, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Interleukin-17A Contributed to the Damage of Blood-CNS Barriers During Streptococcus suis Meningitis - Lei Xu; Xi Lu; Peng Xiao; Ran Liu; Kunlong Xia; Meizhou Wu; Meilin Jin; Anding Zhang (Molecular Neurobiology, 2022)

Prediction of the Influence of Runner Tip Clearance on the Performance of Tubular Turbine - Yanzhao Wu; Xiaohang Wang; Xiaolong Yang; Junfeng Ding; Di Zhu; Ran Tao; Huanmao Wang; Ruofu Xiao (Journal of Marine Science and Engineering, 2022)
Tubular turbine is a type of turbine with low-head. Due to the fact that the runner of a tubular turbine is of axial-flow type, there will be a certain width of blade tip between the blade and the chamber. In order to explore the influence of tip clearance width on the flow inside the turbine, taking the model tubular turbine as the research object, six different tip clearance widths were compared and analyzed. The research shows that the increase in blade tip clearance width affects the performance of the turbine, reduces the minimum pressure at blade tip and causes cavitation in advance. Larger tip clearance width significantly increases pressure pulsation intensity inside the turbine, especially in the vaneless region between the runner and guide vane and the area of the runner tip. However, the increase in tip clearance width can greatly reduce the axial force for about 100 N and radial excitation force for about 50% of rotating parts. Therefore, during the design and processing of tubular turbines, the blade tip clearance width should be carefully selected to ensure safe and stable operation of the unit.

Genome resequencing-based high-density genetic map and QTL detection for yield and fiber quality traits in diploid Asiatic cotton (Gossypium arboreum) - Yaohua Li; Tong Mo; Lingfang Ran; Jianyan Zeng; Chuannan Wang; Aimin Liang; Yonglu Dai; Yiping Wu; Ziman Zhong; Yuehua Xiao (Molecular Genetics and Genomics, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Nitratireductor mangrovi sp. nov., a Nitrate-Reducing Bacterium Isolated from Mangrove Soil - Yanghui Ye; Cen Yan; Yanfang Nie; Jianwei Zhang; Zhe Zhao; Ran Zhang; Chuan Xiao; Min Wu (Current Microbiology, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Quantitative Structure-Property Relationship for pH-Triggered Drug Release Performance of Acid-Responsive Four/Six-Arms Star Polymeric Micelles - Ran Zhang; Li-yang Wen; Wen-sheng Wu; Xiao-zhe Yuan; Li-juan Zhang (Pharmaceutical Research, 2019)

Structure–activity relationship investigation of coumarin–chalcone hybrids with diverse side-chains as acetylcholinesterase and butyrylcholinesterase inhibitors - Lu Kang; Xiao-Hui Gao; Hao-Ran Liu; Xue Men; Hong-Nian Wu; Pei-Wu Cui; Eric Oldfield; Jian-Ye Yan (Molecular Diversity, 2018)

Monazite behaviour during isothermal decompression in pelitic granulites: a case study from Dinggye, Tibetan Himalaya - Jia-Min Wang; Fu-Yuan Wu; Daniela Rubatto; Shi-Ran Liu; Jin-Jiang Zhang; Xiao-Chi Liu; Lei Yang (Contributions to Mineralogy and Petrology, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Efficacy of vaccination and nisin Z treatments to eliminate intramammary Staphylococcus aureus infection in lactating cows - Ran Guan; Jun-qiang Wu; Wei Xu; Xiao-yan Su; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2017)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

A high frequency of allopolyploid speciation in the gymnospermous genus E phedra and its possible association with some biological and ecological features - Hui Wu; Zhen Ma; Ming‐Ming Wang; Ai‐Li Qin; Jin‐Hua Ran; Xiao‐Quan Wang (Molecular Ecology, 2016)
The origin and evolution of polyploids have been studied extensively in angiosperms and ferns but very rarely in gymnosperms. With the exception of three species of conifers, all natural polyploid species of gymnosperms belong to Ephedra , in which more than half of the species show polyploid cytotypes. Here, we investigated the origin and evolution of polyploids of Ephedra distributed in the Qinghai–Tibetan Plateau ( QTP ) and neighbouring areas. Flow cytometry ( FCM ) was used to measure the ploidy levels of the sampled species that are represented by multiple individuals from different populations, and then, two single‐copy nuclear genes ( LFY and DDB 2) and two chloroplast DNA fragments were used to unravel the possible origins and maternal donors of the polyploids. The results indicate that the studied polyploid species are allopolyploids, and suggest that allotetraploidy is a dominant mode of speciation in Ephedra . The high percentage of polyploids in the genus could be related to some of its biological attributes such as vegetative propagation, a relatively high rate of unreduced gamete formation, and a small genome size relative to most other gymnosperms. Significant ecological divergences between allotetraploids and their putative progenitors were detected by PCA s and anova and Tukey's tests, with the exception of E. saxatilis . The overlap of geographical distributions and ecological niches of some diploid species could have provided opportunities for interspecific hybridization and allopolyploid speciation.

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Paradevosia shaoguanensis gen. nov., sp. nov., Isolated from a Coking Wastewater - Shuang Geng; Xin-Chi Pan; Ran Mei; Ya-Nan Wang; Ji-Quan Sun; Xue-Ying Liu; Yue-Qin Tang; Xiao-Lei Wu (Current Microbiology, 2015)

Nitratireductor shengliensis sp. nov., Isolated from an Oil-Polluted Saline Soil - Xin-Chi Pan; Shuang Geng; Ran Mei; Ya-Nan Wang; Hua Cai; Xue-Ying Liu; Yue-Qin Tang; Yong Nie; Si-Yuan Ye; Xiao-Lei Wu (Current Microbiology, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Ottowia shaoguanensis sp. nov., Isolated From Coking Wastewater - Shuang Geng; Xin-Chi Pan; Ran Mei; Ya-Nan Wang; Ji-Quan Sun; Xue-Ying Liu; Yue-Qin Tang; Xiao-Lei Wu (Current Microbiology, 2014)

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)

Effect of different dietary raw to pre-gelatinized starch ratios on growth performance, feed utilization and body composition of juvenile yellowfin seabream (Sparus latus) - Xiao-Yi Wu; Yong-Jian Liu; Li-Xia Tian; Kang-Sen Mai; Ran Guo; Sheng-Jie Jin (Aquaculture International, 2007)